APLIKASI PERHITUNGAN KEY PERFORMANCE INDICATORS (KPI) JURUSAN BERBASIS WEBSITE PADA INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA BANDAR LAMPUNG - Arkhiansyah, Yuni; -, Rasikun (Jurnal Informatika, 2018)
Key Performance Indicator (KPI) is the instrument used to manage and process certain activities which are able to be followed, controlled, ensured, and actualized so that the performance is implemented. KPI of each department is one of the benchmarks to know the quality of a university. This program is used to provide solutions for considering the KPI of each department in order to be implemented quickly and efficiently. Therefore, it does not require a long time and can be done anywhere.In this research, this application was built by using Waterfall method as the software development method including 5 stages: planning, analysis, design, implementation, and maintenance. In addition, the programming language used in this research was PHP and HTML. Moreover, the website display used in this research was CSS. Besides, the database used in this research was MySql with Notepad ++. Furthermore, the tool and editor used in this research were Notepad ++ and XAMPP. The result of this research generated the website-based application for KPI in the Informatics and Business Institute Darmajaya Bandar Lampung. The advantage of this application was providing convenience in considering KPI of each department, particularly for the head of each department as the user.Â Keywords: Key Performance Indicators of Department, Waterfall, Website